Phosphatidylinositol 4, 5‐bisphosphate controls Rab7 and PLEKMH1 membrane cycling during autophagosome–lysosome fusion. (13th March 2019) - Baba, Takashi; Toth, Daniel J; Sengupta, Nivedita; Kim, Yeun Ju; Balla, Tamas
Abstract: The small GTPase Rab7 is a key organizer of receptor sorting and lysosomal degradation by recruiting of a variety of effectors depending on its GDP/GTP‐bound state. However, molecular mechanisms that trigger Rab7 inactivation remain elusive. Here we find that, among the endosomal pools, Rab7‐positive compartments possess the highest level of PI4P, which is primarily produced by PI4K2A kinase. Acute conversion of this endosomal PI4P to PI(4, 5)P2 causes Rab7 dissociation from late endosomes and releases a regulator of autophagosome–lysosome fusion, PLEKHM1, from the membrane. Rab7 effectors Vps35 and RILP are not affected by acute PI(4, 5)P2 production. Deletion of PI4K2A greatly reduces PIP5Kγ‐mediated PI(4, 5)P2 production in Rab7‐positive endosomes leading to impaired Rab7 inactivation and increased number of LC3‐positive structures with defective autophagosome–lysosome fusion. These results reveal a late endosomal PI4P‐PI(4, 5)P2 ‐dependent regulatory loop that impacts autophagosome flux by affecting Rab7 cycling and PLEKHM1 association. Synopsis: Phosphoinositides are key regulators of small GTP‐binding proteins, but how they control the activity of Rab GTPases is poorly understood. PI4K2A and PIP5Kγ act sequentially to generate PI(4, 5)P2, which promotes membrane fusion during autophagy through Rab7 inactivation and PLEKMH1 release from late endosomes. PI4K2A is key for PI4P production in Rab7‐positive endosomes. PIP5Kγ converts PI4P to PI(4, 5)P2 at late endosomes to inactivate Rab7. PI4K2A or PIP5Kγ depletion impairs acidification of autophagosomes. The conversion of PI4P to PI(4, 5)P2 promotes the release of PLEKHM1 from late endosome. Abstract : PI4K2A and PIP5Kγ act sequentially to generate PI(4, 5)P2, which promotes membrane fusion during autophagy through Rab7 inactivation and PLEKMH1 release from late endosomes.